Data Storage Issues in Smart Cities and Smart Environments - Horák, Oldřich; Tykva, Radek (International Business Information Management Association-IBIMA, 2019)
This article describes the basic points of view on data storage issues in smart environments mainly related to Smart Cities. The Smart Cities can generate large amounts of raw data that often need to be stored in large data repositories and storage. This brings with it several questions and tasks related to the Total Cost of Ownership of data repositories and their administration. Some important points on these issues are described in this article. In the conclusion, the next steps of future work in research in this field are introduced.
Problémy s ukládáním dat v chytrých městech a chytrých prostředích
Keywords: Smart Cities; Data Storage; Smart Environments; TCO; Chytrá města; Datová úložiště; Chytrá prostředí; TCO